Comparison of PHQ-9 and PHQ-2 as Screening Tools for Depression and School Related Stress in Inner City Adolescents - Paridhi Anand; Navpreet Bhurji; Nadia Williams; Ninad Desai (SAGE Publishing, 2021)
Background Major depressive disorder is associated with significant morbidity and mortality in adolescents. Suicide is one of the leading causes of mortality between 15 and 19 years. Both AAP and USPSTF recommend routine depression screening of adolescents. Patient Health Questionnaire-2 (PHQ-2) and Patient Health Questionnaire-9 (PHQ-9) are widely used in primary care practice, however, PHQ-2 does not screen for suicidality. School-related factors are known to affect adolescent mental health. Purpose To compare PHQ-2 and PHQ-9 for depression screening in adolescents, with respect to age, gender, chronic illness over the course of 9 months. Methods As a QI initiative, we compared screening results in our inner-city pediatric practice using PHQ-2 and PHQ-9 from Jun'18 to Feb'19. EMR of 2364 patients 12 to 21 years were reviewed. We considered the PHQ-2 score of ≥2 and PHQ-9 of ≥10 as positive. Pre-existing chronic medical and mental illnesses were noted. Results Of these 61.5% of patients were females, 95% were Black/Hispanic, and 96% were insured by Medicaid. About 10.6% of PHQ-9 tests were positive whereas 7.4% PHQ2 were positive. Logistic regression was performed to ascertain the effects of age, gender, and chronic illness. Females were more likely to have a positive screen, as were patients with chronic illness. Age had no effect on the outcome. The screening yield for both tests was comparable in the summer months. PHQ9 yield increased while schools were in session while PHQ 2 remained stable. Conclusion PHQ9 is superior as a screening test compared to PHQ2. Repeat screening should be targeted toward patients with chronic medical conditions and/or mental health diagnoses. PHQ9 may be better at screening for school-related stress.